Kontribusi Dukungan Sosial terhadap Kesehatan Mental Mahasiswa Rantau - Alessia Lirion Pui; Meike Kurniawati (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2024)
Migrant students often face psychological challenges while pursuing higher education away from their hometowns, including academic pressure, loneliness, and the need to adapt to new environments. These conditions can affect their mental balance if not supported by adequate social relationships. This study aims to examine how social support contributes to the mental health of migrant college students. The research used a quantitative approach with a correlational explanatory design. Data were collected from 214 migrant students through an online questionnaire measuring levels of social support and positive mental health. Analysis was conducted using simple linear regression to identify the relationship between the two variables. The results showed that higher levels of social support are associated with better mental health among migrant students. Support from family, friends, and significant others helps them manage stress, build a sense of security, and maintain optimism throughout their academic journey. These findings highlight the importance of social support as a protective factor that strengthens psychological well-being among students living away from their familiar environment.